Structural, Morphological, and Some Optical Properties of Amorphous and Polycrystalline Lead Oxide Thin Films - Sh. Hashim, Fouad; A. Mohaimeed, Ameen (Al-Qadisiyah Journal of Pure Science, 2018)
Lead oxide (PbO) thin films were deposited on unheated glass substrates, using the vacuum thermal deposition with a rate of deposition 0.7 nm/ s, at 130nm thickness .The annealing temperature was varied from 523 to 723K for 2 hr . X-ray diffraction (XRD) analysis was used to study the structural and crystallite size of PbO thin film. Before annealing effect, the XRD results indicated that the PbO film is in amorphous nature . After annealing, the corresponding diffraction patterns revealed that the films crystallize in polycrystalline mixed compounds of (PbOtet), and (PbOorth) with a preferred orientation along (020) plane. The average crystallite sizes estimated from XRD data was found to lie in the range of 15.11 – 36.80 nm. The surfaces morphology of these films was studied by the Atomic Force Microscopy (AFM) studies. AFM confirmed that the PbO films have good homogeneous surface. The roughness average, and root mean square values increased with the increasing annealing temperatures . The higher optical transmittance value of PbO film annealed at 523K was found to lie in the range of 88-91% in VIS and IR regions respectively. The optical properties showed that the PbO thin films have allowed direct transitions and the values of energy gap decreased with increasing annealing temperature.